2020
DOI: 10.18632/oncotarget.27342
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical activity of sacituzumab govitecan (IMMU-132) in uterine and ovarian carcinosarcomas

Abstract: Background: Uterine and ovarian carcinosarcomas (CS) are rare cancers with poor prognosis. Sacituzumab-govitecan (SG) is a new class of antibody-drug-conjugate (ADC) targeting the human-trophoblast-cell-surface marker (Trop-2) conjugated with the active metabolite of irinotecan (SN-38). We evaluated the efficacy of SG against biologically aggressive CS.Methods: Trop-2 expression was evaluated in 10 formalin-fixed-paraffinedembedded (FFPE) CS by immunohistochemistry and 9 primary CS cell-lines by flowcytometry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 34 publications
(44 reference statements)
0
29
0
3
Order By: Relevance
“…6,45 These data are in line with earlier preclinical studies of uterine, ovarian, and endometrial adenocarcinoma models, all of which overexpress Trop-2, where SG demonstrated a significant in vitro cytotoxic effect on primary Trop-2-positive cell lines, a significant bystander killing effect in the tumor microenvironment, and antitumor effects in Trop-2-positive xenograft models. [46][47][48] A study of SG in endometrial carcinoma is underway in Trop-2-enriched patients to determine whether additional efficacy may be achieved by selecting patients with high Trop-2-expressing tumors (NCT04251416).…”
Section: Discussionmentioning
confidence: 99%
“…6,45 These data are in line with earlier preclinical studies of uterine, ovarian, and endometrial adenocarcinoma models, all of which overexpress Trop-2, where SG demonstrated a significant in vitro cytotoxic effect on primary Trop-2-positive cell lines, a significant bystander killing effect in the tumor microenvironment, and antitumor effects in Trop-2-positive xenograft models. [46][47][48] A study of SG in endometrial carcinoma is underway in Trop-2-enriched patients to determine whether additional efficacy may be achieved by selecting patients with high Trop-2-expressing tumors (NCT04251416).…”
Section: Discussionmentioning
confidence: 99%
“…6,[8][9][10] Its proprietary linker also allows SN-38 to be liberated in the tumor microenvironment, enabling antitumor effects (bystander effect) without prerequisite internalization and enzymatic cleavage of SN-38 from the anti-Trop-2 antibody. 6,8,11 As BRCA1 or BRCA2 (BRCA1/2) confer a deficiency in homologous recombination repair of double-stranded DNA breaks, there is interest in BRCA1/2 as a potential biomarker of response for therapy regimens that target DNA damage, particularly for TNBC. 12 Approximately 15% of patients with TNBC have germline BRCA mutations, a higher prevalence compared with other breast cancer subtypes.…”
Section: Conclusion: Sg Benefits Patients With Previously Treated Mtnbc Expressing High/mediummentioning
confidence: 99%
“…Based on results of phase II trials in small cell lung carcinoma and non-small cell lung carcinoma, SG also gained Fast Tract designation from the US FDA for these conditions. Overall, SG holds great promise in the field of ADCs, as supported by SG data of remarkable preclinical potency in tumors, including ovarian, 74 uterine, 75 and cervical 76 cancers.…”
Section: Fam-trastuzumab Deruxtecan (Enhertu ® Ds-8201a)mentioning
confidence: 88%